2016
DOI: 10.1021/acs.bioconjchem.6b00529
|View full text |Cite
|
Sign up to set email alerts
|

Universal Biotin–PEG-Linked Gold Nanoparticle Probes for the Simultaneous Detection of Nucleic Acids and Proteins

Abstract: Novel biotin—polyethylene glycol (biotin—PEG) gold nanoparticle probes have been synthesized and used as universal constructs for the detection of protein (prostate-specific antigen, PSA) and nucleic acid targets (microRNAs) from a single sample. Microarray assays based upon these probes enabled sensitive detection of biomarker targets (50 fM for nucleic acid targets and 1 pg/μL for the PSA target). Ways of detecting biomarkers, including nucleic acids and proteins, are necessary for the clinical diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 58 publications
0
23
0
Order By: Relevance
“…MicroRNAs (miRNAs) are recognized as critical regulators of multiple biological processes in cancer, breast cancer in particular, including tumorigenesis, tumor progression, stress response, and drug resistance . Since miRNA discovery, increasing evidence has indicated their essential roles in tumor progression and metastasis; therefore, miRNAs have emerged as potential biomarkers for cancer diagnosis, prognosis, and/or treatment efficacy . Thus, it was shown that miRNA expression patterns correlate with breast cancer subtype and the hormone receptor status …”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are recognized as critical regulators of multiple biological processes in cancer, breast cancer in particular, including tumorigenesis, tumor progression, stress response, and drug resistance . Since miRNA discovery, increasing evidence has indicated their essential roles in tumor progression and metastasis; therefore, miRNAs have emerged as potential biomarkers for cancer diagnosis, prognosis, and/or treatment efficacy . Thus, it was shown that miRNA expression patterns correlate with breast cancer subtype and the hormone receptor status …”
Section: Introductionmentioning
confidence: 99%
“…A very interesting microarray assay that uses gold nanoparticle probes for the simultaneous detection of RNA and proteins was recently reported by the Mirkin group. [142] The strategy involved the capture of biotinylated RNA on the microarray slide, followed by the labeling with gold nanoparticles. The read-out was accomplished by using the light scattering of the conjugated gold nanoparticles.…”
Section: Comparison Of Qd-based Otr To Other Methods In the Fieldmentioning
confidence: 99%
“…Studies have been reported for the synthesis of AuNPs functionalized with lectin, lactose, and biotin along-with PEG. [197][198][199] Such functionalized AuNPs cannot only be used for cellular internalization but for intracellular internalization as well. PEGlyated gold nanoparticles can also be conjugated with thiol having florescent dye coumarin attached on one side.…”
Section: Peglyation Of Aunpsmentioning
confidence: 99%